2011
DOI: 10.1021/ja201726q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Computational Studies of Oxidatively-Induced Aryl−CF3 Bond-Formation at Pd: Rational Design of Room Temperature Aryl Trifluoromethylation

Abstract: This article describes the rational design of 1st generation systems for oxidatively-induced Aryl–CF3 bond-forming reductive elimination from PdII. Treatment of (dtbpy)PdII(Aryl)(CF3) (dtbpy = di-tert-butylbipyridine) with NFTPT (N-fluoro-1,3,5-trimethylpyridium triflate) afforded the isolable PdIV intermediate (dtbpy)PdIV(Aryl)(CF3)(F)(OTf). Thermolysis of this complex at 80 °C resulted in Aryl–CF3 bond-formation. Detailed experimental and computational mechanistic studies have been conducted to gain insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(73 citation statements)
references
References 95 publications
3
68
0
2
Order By: Relevance
“…Trifluoromethylation has, in the past, relied on the use of transition metal catalysts, such as those containing Pd [22][23][24][25][26][27][28][29][30][31][32] and Cu [33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Photoredox catalytic trifluoromethylation, fluoroalkylation and fluorination reactions provide a promising alternative to these existing methods, as it utilizes the environmentally benign protocols that rely on visible light or even sunlight irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Trifluoromethylation has, in the past, relied on the use of transition metal catalysts, such as those containing Pd [22][23][24][25][26][27][28][29][30][31][32] and Cu [33][34][35][36][37][38][39][40][41][42][43][44][45][46] . Photoredox catalytic trifluoromethylation, fluoroalkylation and fluorination reactions provide a promising alternative to these existing methods, as it utilizes the environmentally benign protocols that rely on visible light or even sunlight irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…201 First they demonstrated that, as expected, the reductive elimination of Ar-CF 3 does not take place from the Pd(II) complex [PdAr(CF 3 )(LL)].…”
Section: Scheme 61mentioning
confidence: 66%
“…Based on the obtained results three transition states may be proposed for the arylation event (Figure 7). TS1: direct insertion of palladium (C3 complex) into the C À I bond (leading to Pd IV complex [40] C4 IV ); TS2: ipso oxidative substitution (leading to Pd IV complex C4 IV ) or TS3: ipso substitution, which would lead to Pd II complex C4 II and upon reductive elimination, formation of aryl À carbon bond, to Pd 0 complex, that would be internally re-oxidized by formed N À I species. A detailed look at the MS spectra for intermediates or side products did not allow us to distinguish between these proposals.…”
Section: Resultsmentioning
confidence: 99%